The Role of Testosterone in The Improvement of Sexual Desire in Postmenopausal Women: An Evidence-Based Clinical Review - Gouveia, Maria (2018)
Introduction: Female sexual dysfunction is a common problem, affecting more than 1/3 of women during their lives. The aim of this review is to review the evidence for the effectiveness of testosterone in sexual dysfunction in postmenopausal women, particularly in the improvement of sexual desire.Material and Methods: The authors searched in international databases National Guidelines Clearinghouse, Guidelines Finder, Cochrane Library and MEDLINE/PubMed, for guidelines, systematic reviews, meta-analysis and randomized controlled trials, published between January 2005 and February 2017, using the MeSH terms ‘testosterone’, ‘androgens’, ‘libido’, ‘sexual dysfunctions’ and ‘menopause’.Results: From a pool of 506 articles, 11 were selected: three guidelines, one systematic review with meta-analysis and seven randomized controlled trials. The selected articles showed testosterone‘s efficacy on global sexual function and improvement of sexual desire in postmenopausal women, when both are used in monotherapy or in association with other hormones. No study showed changes in hepatic enzymes or serious adverse effects.Discussion: The small sample size and short follow-up used in the included studies limits the ability to assess testosterone’s long-term benefits and effects.Conclusion: At short-term, testosterone seems to improve sexual function in postmenopausal women, particularly sexual desire. Nevertheless, more studies with larger sample size and longer follow-up are needed to understand its long-term safety and effectiveness.